MODERASI BERAGAMA DAN RELEVANSINYA BAGI KEHIDUPAN IMAN ORANG MUDA KATOLIK DI PAROKI SANTA MARIA RATU OEOLO - Kolo, Florida Maria Regina; Sesfao, Marianus; Aek Klau, Yohana (JURNAL PROPHETA, 2025)
The diversity of the Indonesian nation is a given—a destiny bestowed by the Creator that must be respected and not taken for granted. Indonesia is home to a vast variety of cultures and religions, nearly unmatched in the world. According to the Central Statistics Agency (BPS) in 2013, there are 1,331 tribes and sub-tribes in Indonesia, or 633 when grouped by major tribe. This study aims to: 1) Identify factors related to religious moderation. 2) Explore the values of religious moderation.The research uses a qualitative method, in which the author describes and explains the research object to categorize and conclude issues related to the understanding of youth in the Santa Maria Ratu Oeolo Parish regarding faith life. Young Catholics (OMK) require guidance from their parents to grow and develop as expected. OMK are an integral part of the Church, serving as examples and role models for others. They must also be able to face internal pressures from social culture and dynamics. Based on the research findings, it is concluded that Catholic Youth (OMK) in Santa Maria Ratu Oeolo Parish wisely avoid engaging in unwanted behaviors, such as alcohol consumption. Through fellowship, they share experiences and talents, which helps OMK better understand and connect with their community.